1. This site uses cookies. By continuing to use this site, you are agreeing to our use of cookies. Learn More.

Discrete Mathematics Proofs for ∃ and ∀

Discussion in 'Computer Science' started by Swaraj, Oct 8, 2018.

  1. Swaraj

    Swaraj Guest

    Premise or Given - ∃x(A(x) → B(x)) ∀x (B(x) → K(x))

    To Prove - ∃x(A(x) → K(x))

    My Solution -

    1) A(z) → B(z) From premise and Existential instantiation x for z

    2) B(z) → K(z) From premise and Universal instantiation x for z

    3) A(z) → K(z) Transitivity of 1,2

    4)∃x(A(x) → K(x)) From Existential Generalization Substitute z for x

    Am I doing this right if not is there any other way to prove it ?

    Login To add answer/comment
     

Share This Page